2016
DOI: 10.1016/j.eneco.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' willingness to contract switchgrass as a cellulosic bioenergy crop in Kansas

Abstract: Farmers' adoption of cellulosic biofuel feedstock enterprises plays an important role in the future of agriculture and the renewable fuels industry. However, no set markets currently exist for bioenergy feedstocks outside of very localized geographic locations and farmers may be reluctant to produce the feedstocks without contracts that help mitigate uncertainty and risk. This study examines farmers' willingness to grow switchgrass under contract using a stated choice approach. Data were collected using an enu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…This result was also found in two studies on the cultivation of energy crops (Khanna et al, 2017;Windle & Rolfe, 2005). In contrast, Fewell, Bergtold, and Williams (2016) and Krah et al (2015) found that the risk attitude had no significant effect on the cultivation of switchgrass and miscanthus. Albeit at a relatively low significance level, the covariate farm size shows a negative part-worth parameter for SRC.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This result was also found in two studies on the cultivation of energy crops (Khanna et al, 2017;Windle & Rolfe, 2005). In contrast, Fewell, Bergtold, and Williams (2016) and Krah et al (2015) found that the risk attitude had no significant effect on the cultivation of switchgrass and miscanthus. Albeit at a relatively low significance level, the covariate farm size shows a negative part-worth parameter for SRC.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, networks involving farmers and the interested processing industry should be initiated or promoted once a largescale material use of lignocellulose seems to be useful and feasible. Analyses by Fewell et al (2016), Khanna et al (2017) and Krah et al (2015) have already illustrated the importance of purchase contracts with respect to the production of energy crops.…”
Section: Discussionmentioning
confidence: 99%
“…In corn stover markets, research finds that long term contracts (3-5 years) are preferable to short-term ones (1-2 years) from a risk management perspective [2]. Conversely, a survey of potential switchgrass growers in Kansas indicated that each year of contract length would increase the payment required by approximately $1 per acre [64].…”
Section: A Narrative Review Of the Literaturementioning
confidence: 96%
“…Predicting the potential supply of land for biomass production in the United States has become the subject of intensive research since the passage of the Energy Independence and Security Act of 2007. A substantial number of authors have addressed the question of the determining factors that drive biomass supply decisions (Jensen et al ., ; Paulrud and Laitila, ; Cope et al ., ; Joshi and Mehmood, ; Tyndall et al ., ; Altman and Sanders, ; Qualls et al ., ; Villamil et al ., ; Aguilar et al ., ; Bergtold et al ., ; Skevas et al ., , ; Altman et al ., ; Mooney et al ., ; Cai et al ., ; Fewell et al ., ). Despite providing valuable insight into factors affecting the supply of land for bioenergy crops, these studies ignore spatial dependence, despite its potential influence on land supply decisions.…”
Section: Introductionmentioning
confidence: 97%